2022
DOI: 10.3390/life12121987
|View full text |Cite
|
Sign up to set email alerts
|

Supplying Bee Pollen and Propolis to Growing Rabbits: Effects on Growth Performance, Blood Metabolites, and Meat Quality

Abstract: The objective of this study was to evaluate the effect of supplementation with bee pollen (BP) and propolis (PRO) on productive performance, Eimeria oocyst counts in feces, blood metabolites, and the meat quality of growing rabbits. A total of 160 hybrid rabbits (California × New Zealand) of 30 days of age and 643 ± 8.0 g body weight (BW) were assigned to four treatments with 10 replicates each (four rabbits/replicate). The treatments were as follows: (1) CON: rabbits fed basal diet and not supplemented with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…FLAs supplementation did not affect the meat's protein, moisture, and ash content; however, the IMF increased. These results indicate that FLAs do not negatively affect the nutritional value of beef since the protein and ash content of the meat are related to its nutritional value ( 93 , 102 ). In contrast, the higher IMF observed could be positive since IMF correlates positively with beef's tenderness and juiciness ( 103 ).…”
Section: Discussionmentioning
confidence: 82%
“…FLAs supplementation did not affect the meat's protein, moisture, and ash content; however, the IMF increased. These results indicate that FLAs do not negatively affect the nutritional value of beef since the protein and ash content of the meat are related to its nutritional value ( 93 , 102 ). In contrast, the higher IMF observed could be positive since IMF correlates positively with beef's tenderness and juiciness ( 103 ).…”
Section: Discussionmentioning
confidence: 82%
“…Administered at the level of 50 µL/kg of body weight Serves as a natural growth promoter and prevents coccidiosis for growing rabbits. [37] Pollen Administered at the level of 5 g/kg of diet Improves quail males' growth performance and body weight gain. [38] Boosts quail hens' egg production and immunological response.…”
Section: Bee Products Administration and Dose Main Results Referencesmentioning
confidence: 99%
“…Thus, this addition can improve growing rabbits' immune response by positively impacting the microbiota in the cecum [36]. Similarly, Sierra-Galicia et al [37] reported that propolis supplementation (50 µL/kg body weight) can work as a natural growth promoter in rabbits and prevent coccidiosis without affecting rabbit health and meat quality.…”
Section: Potential Effects Of Bee Products On Poultry and Rabbit Perf...mentioning
confidence: 94%
“…Zeedan et al, (2017) indicated that bee pollen contained 29.94 %CP, 1.17% CF , 2.83 % ash and 4.35% EE on DM basis. Sierra-Galicia et al, (2022) showed that the chemical analysis of the PRO was 90.26% DM, 2.55% CP, 9.31% EE, and 0.85% ash. Fayed et al, (2012) concluded that PPP gave 3.65 CP, 0.61% EE, 23.4% CF and 5.4% ash.…”
Section: Chemical Composition Of Feed Additivesmentioning
confidence: 99%
“…PRO has antioxidant, immune-stimulant, and antimicrobial properties (Hashem et al, 2017), due to its high satisfied of polyphenols components as flavonoids and phenolic acids (Bhargava et al, 2021). many studies investigated the effectiveness of PRO addition on growing rabbits by supplying in capsules form ( Attia et al, 2019 a andAttia et al, 2019 b), in drinking water (Sierra-Galicia et al, 2022), orally suspension (El-Kott and Owayss ;Attia et al, 2015Attia et al, 2011a or b ) or by mixing into the basal diet (Hashem et al, 2017;Waly et al, 2021;Al-Homidan et al, 2022). These previous studies showed that PRO supplementation in the diet improved serum immunoglobulin concentration , enhanced cecum health and decreases the attendance of pathogenic bacteria, increased the antioxidant profile of the birds (Hashem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%